Chronic Exertional Compartment Syndrome of the Forearm: Mini-invasive Technique Using an Endoscopic Soft Tissue Release System. Issue 2 (20th June 2021) - Tamborini, Federico; Minini, Andrea; Garutti, Leonardo; Smeraglia, Francesco; Valdatta, Luigi; Cherubino, Mario
Abstract : Supplemental Digital Content is available in the text. Abstract : Chronic exertional compartment syndrome of the forearm is a rare disease characterized by the recurrent onset of forearm pain and progressive weakness during exertion. Over the years many surgical techniques have been reported in literature: wide-open fasciotomy, mini-open fasciotomy, fasciotomy associated with fasciectomy, and mini-invasive endoscopic fasciotomy. Compared with traditional open techniques, mini-invasive techniques are characterized by minimal tissue trauma, less postoperative pain, faster recovery to normal activity and better esthetical result. We describe a mini-invasive endoscopic technique for the treatment of forearm chronic exertional compartment syndrome using the SmartRelease endoscopic tissue release system (MicroAire).